Application of D-CRDM Method in Columnar Jointed Basalts Failure Analysis. (24th September 2013) - Jin, Changyu; Feng, Xiating; Yang, Chengxiang; Fang, Dan; Liu, Jiangpo; Xu, Shuai
Abstract : Columnar jointed basalt is a type of joint rock mass formed by the combined cutting effect of original joints and aphanitic microcracks. After excavation unloading, such rock mass manifested distinct mechanical properties including discontinuity, anisotropy, and proneness of cracking. On the basis of former research findings, this paper establishes a D-CRDM method applicable to the analysis of columnar jointed basalt, which not only integrates discrete element and equivalent finite-element methods, but also takes into account the coupling effect of original joints and aphanitic microcracks. From the comparative study of field monitoring data and strain softening constitutive model calculated results, it can be found that this method may well be used for the simulation of mechanical properties of columnar jointed basalts and the determination of rock failure mechanism and failure modes, thus providing references for the selection of supporting measures for this type of rock mass.